ATP-driven chromatin remodeling activity and histone acetyltransferases act sequentially during transactivation by RAR/RXR in vitro. - Dilworth, F.J.; Fromental-Ramain, C.; Yamamoto, K.; Chambon, P. (Molecular Cell, 2000)
Using a "crude" chromatin-based transcription system that mimics transactivation by RAR/RXR heterodimers in vivo, we could not demonstrate that chromatin remodeling was required to relieve nucleosomal repression. Using "purified" chromatin templates, we show here that, irrespective of the presence of histone H1, both ATP-driven chromatin remodeling activities and histone acetyltransferase (HAT) activities of coactivators recruited by liganded receptors are required to achieve transactivation. DNA footprinting, ChIP analysis, and order of addition experiments indicate that coactivator HAT activities and two ATP-driven remodeling activities are sequentially involved at distinct steps preceding initiation of transcription. Thus, both ATP-driven chromatin remodeling and HAT activities act in a temporally ordered and interdependent manner to alleviate the repressive effects of nucleosomal histones on transcription by RARalpha/RXRalpha heterodimers.